2016
DOI: 10.1089/thy.2015.0482
|View full text |Cite
|
Sign up to set email alerts
|

124I PET/CT in Patients with Differentiated Thyroid Cancer: Clinical and Quantitative Image Analysis

Abstract: (124)I PET/CT is a valuable clinical imaging tool/agent, both in determining the extent of disease in the setting of metastatic DTC and in the functional volumetric and kinetic evaluation of target lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…There were four studies that were prospective (Phan et al ., Capocetti et al ., Gulec et al . and Kist et al …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…There were four studies that were prospective (Phan et al ., Capocetti et al ., Gulec et al . and Kist et al …”
Section: Resultsmentioning
confidence: 94%
“…Eight studies were initially identified in the systematic review as potentially qualified for inclusion in the meta‐analysis . On further assessment, three of these studies were excluded .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of I-124 in clinical practice in a patient with DTC was first described in 1960 ( 1 ), and the first PET-based dosimetry study based on serial measurements in DTC patients was published in 1999 ( 2 ) after phantom studies demonstrated that quantification was feasible ( 3 ). Since then, there have been several key articles demonstrating the clinical utility of I-124 and its role in the detection of residual thyroid tissue and/or metastasis in patients with DTC ( 4 , 5 , 6 , 7 , 8 ); and the following are some more recent highlights.…”
Section: History Of I-124 In Clinical Practicementioning
confidence: 99%
“…Additionally TKI-PET tracers have shown encouraging results [63] . Finally, 124 I-PET has demonstrated clinical and functional value in the analysis of DTC metastases [64,65] .…”
Section: Molecular Imagingmentioning
confidence: 99%